Circumscribed Storiform Collagenoma Associated with Rubinstein-Taybi Syndrome in a Young Adolescent - Nick Zavras; Rosario Mennonna; Spyros Maris; George Vaos (Karger Publishers, 2016)
Rubinstein-Taybi syndrome is a rare congenital neurodevelopmental disorder characterized by dysmorphic features, skeletal abnormalities, growth deficiency, and mental retardation. Circumscribed storiform collagenoma is a distinct benign fibromatous tumor that presents either as solitary tumor or in association with other syndromes. In this report, we describe a 16-year-old male with Rubinstein-Taybi syndrome associated with circumscribed storiform collagenoma. To our knowledge, this association has not been previously described in the literature.